Pemetaan Kebutuhan Pendampingan Konseling: Study of Psychological Wellbeing on Students with Disabilities - Rahma, Ulifa; Hikmiah, Ziadatul; Firmanda, Tommy Hari (PLD UIN Sunan Kalijaga, 2022)
The most prominent discrimination against persons with disabilities (PwD) is exclusion in education opportunity, even though the rights of persons with disabilities to pursue education have been guaranteed by the Convention on the Rights of Persons with Disabilities (CRPD). The research is the first step for an effective model of counseling services for students with disabilities. Rule Mapping for counseling with qualitative research carries out with three methods under the online survey, the Nominal Group Technique (NGT), and Focus Group Discussion (FGD. With 33 Respondents for the study are the students with intellectual and mental disabilities, Deaf, blind, and physically disabled. Data use interactive and thematic analysis. The result shows an overview with map counselling for students with disabilities on services. Diskriminasi yang paling menonjol terhadap penyandang disabilitas (PD) adalah pengecualian mereka dalam kesempatan pendidikan yang setara, padahal hak PD untuk mengenyam pendidikan sudah dijamin oleh Konvensi Hak-Hak Penyandang Disabilitas (CRPD). Penelitian ini merupakan langkah awal untuk model layanan konseling yang efektif bagi siswa PD. Rule Mapping digunakan untuk melakukan konseling pada penelitian ini. Penelitian ini merupakan penelitian kualitatif yang dilakukan dengan tiga metode di antaranya survei online, Nominal Group Technique (NGT), dan Focus Group Discussion (FGD). Terdapat 33 siswa dengan disabilitas mental-intelektual, Tuli, Buta, dan fisik) yang dilibatkan dalam penelitian ini. Analisis data menggunakan teknik interaktif dan tematik. Hasil penelitian menunjukkan gambaran dengan peta konseling untuk siswa PD dalam menerima layanan.